(untitled) (Global Journal of Medical Research, 2023)
Background The gold standard for surgical treatment of LUTS brought on by BPH is transurethral resection of the prostate TURP The purpose of this treatment is to reduce LUTS brought on by BPH and enhance the patient s quality of life When assessing this therapy objective and developing post-TURP care for individuals who still experience symptoms evaluation of post-TURP symptomatic alleviation is essential Aim To evaluate the patients quality of life and the IPSS score for voiding and storage symptoms in relation to the remission of LUTS caused by BPH after TURP Methods In the Institute of Urology of KCMC Moshi Tanzania patients who underwent TURP for symptomatic BPH participated in this 6-month hospital prospective observational study We ll figure out the IPSS and QoLS before and after surgery